Conceptual Metaphors of Alienation and Disappointment in Radiohead's “Let Down” - Ilham Yafi Pramono; wiwiek afifah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Song lyrics play an important role in expressing complex emotional experiences that are often difficult to articulate through literal language. Although previous studies have examined metaphor and emotion in music, many focus on large corpora or musical structure, leaving a gap in close, lyric-centered analyses of how emotional meaning is constructed within individual songs. This study addresses that gap by examining how emotional experience is structured through conceptual metaphor in Radiohead’s song “Let Down.” Grounded in Conceptual Metaphor Theory, this research focuses on three interrelated frameworks: Emotion Is a Physical Force, The Object Event-Structure Metaphor, and Force Dynamics. Using a qualitative descriptive approach, the lyrics are analyzed to identify recurring metaphorical patterns related to alienation, disappointment, and longing. The findings reveal that emotional suffering is consistently framed as embodied and overwhelming, while the lyrical subject is positioned as a passive entity subjected to repeated emotional events. Movement imagery further reflects constrained emotional effort, resulting in frustration rather than change. These results suggest that metaphor in song lyrics functions as a cognitive mechanism that enables listeners to experience emotion as embodied and enduring